Evaluation of hospital portals using knowledge management mechanisms - Lee, Chei Sian (2009)
Hospital portals are becoming increasingly popular since they play an important role to provide, acquire and exchange information. Knowledge management (KM) mechanisms will be useful to hospitals that need to manage health related information, and to exchange and share information with their patients and visitors. This paper presents a comprehensive analysis of knowledge management mechanisms used by 20 hospital portals from North America and Asia to access, create and transfer knowledge. We developed a systematic and structured approach to evaluate how well the portals captured and delivered information to patients and visitors about the hospitals’ business processes, products, services, and customers from the perspective of three KM mechanisms (i.e. knowledge access, knowledge creation and knowledge transfer). Our results show that our selected hospital portals provided varying degrees of support for these KM mechanisms.